Comparison of serum cytokine profiles in macrophage activation syndrome complicating different background rheumatic diseases in children. (18th July 2020) - Mizuta, Mao; Shimizu, Masaki; Irabu, Hitoshi; Usami, Masaaki; Inoue, Natsumi; Nakagishi, Yasuo; Wada, Taizo; Yachie, Akihiro
Abstract: Objectives: To compare the cytokines involved in the development of macrophage activation syndrome (MAS) in different background rheumatic diseases and to identify serum biomarkers for MAS diagnosis. Methods: Serum neopterin, IL-6, IL-18 and soluble TNF receptor (sTNFR) type I (sTNFR-I) and type II (sTNFR-II) levels were determined using ELISA in 12 patients with SLE, including five with MAS; 12 patients with JDM, including four with MAS; 75 patients with Kawasaki disease (KD), including six with MAS; and 179 patients with systemic JIA (s-JIA), including 43 with MAS. These results were compared with the clinical features of MAS. Results: Serum neopterin, IL-18 and sTNFR-II levels were significantly higher during the MAS phase than during the active phase in patients with all diseases. Furthermore, serum sTNFR-I levels were significantly higher during the MAS phase than during the active phase in patients with SLE, KD and s-JIA. Receiver operating characteristic (ROC) curve analysis revealed that serum sTNFR-I levels for SLE, serum IL-18 levels for JDM, and serum sTNFR-II levels for KD and s-JIA had the highest areas under the ROC curve. Serum levels of these cytokines were significantly and positively correlated with serum ferritin levels. Conclusions: Overproduction of IFN-γ, IL-18 and TNF-α might be closely related to the development of MAS. Serum levels of sTNFR-I for SLE, IL-18 for JDM, and sTNFR-II for KD and s-JIA might be useful diagnostic markers for the transition from active phase to MAS.